2010
DOI: 10.1080/09640560903399772
|View full text |Cite
|
Sign up to set email alerts
|

Moving from agenda to action: evaluating local climate change action plans

Abstract: Climate change is conventionally recognised as a large-scale issue resolved through regional or national policy initiatives. However, little research has been done to directly evaluate local climate change action plans. This study examines 40 recently adopted local climate change action plans in the US and analyses how well they recognise the concepts of climate change and prepare for climate change mitigation and adaptation. The results indicate that local climate change action plans have a high level of 'awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(180 citation statements)
references
References 51 publications
4
175
0
1
Order By: Relevance
“…This is contrary to other parts of the world as outlined by a global survey of 468 cities, conducted by the Massachusetts Institute of Technology (Carmin et al, 2012), which found membership to organizations linking and working with local governments to sustainable practices (such as ICLEI) boosting action to adapt to climate change. Further, examining 40 local climate change action plans in the US points out that these plans have typically "a high level of awareness", moderate "analysis capabilities" for climate change, and relatively limited "action approaches" for climate change mitigation" (Tang et al, 2010). This is also supported by an assessment of the available best practices in both mitigation and adaptation for North American cities, highlighting the need for increased attention to adaptation at the local level (Zimmerman and Faris, 2011).…”
Section: Policies and Strategies: From National To Local Levelsmentioning
confidence: 99%
“…This is contrary to other parts of the world as outlined by a global survey of 468 cities, conducted by the Massachusetts Institute of Technology (Carmin et al, 2012), which found membership to organizations linking and working with local governments to sustainable practices (such as ICLEI) boosting action to adapt to climate change. Further, examining 40 local climate change action plans in the US points out that these plans have typically "a high level of awareness", moderate "analysis capabilities" for climate change, and relatively limited "action approaches" for climate change mitigation" (Tang et al, 2010). This is also supported by an assessment of the available best practices in both mitigation and adaptation for North American cities, highlighting the need for increased attention to adaptation at the local level (Zimmerman and Faris, 2011).…”
Section: Policies and Strategies: From National To Local Levelsmentioning
confidence: 99%
“…Among the most basic needs are climate change awareness and technical knowledge of how to proceed; Australian research has found that planners express uncertainty about how to begin CCA planning, despite evident awareness and conviction about the need for action (Measham et al, 2011, Baker et al, 2012, Gurran et al, 2012a. Consistently, if regulatory authority or mandates to support adaptation efforts are absent, it is much more difficult for planners overcome local barriers arising from insufficient information and capacity constraints (Few et al, 2007, Funfgeld, 2010, Tang et al, 2010. State mandates, while sometimes viewed by local officials as obtrusive and controlling without the benefit of additional funding, can provide both an alignment of values and the political cover needed when facing opposition from constituents (Bedsworth & Hanak, 2010;Dalton & Burby, 1994).…”
Section: Barriers To Adaptation Actionmentioning
confidence: 99%
“…‱ political changes, such as the election of a new leader who makes responding to climate change a priority (Ford et al, 2011) ‱ pressure from citizens for protection from the effects of climate change (Sippel and Jenssen, 2009) ‱ local government's desire to have a "green" reputation to attract new businesses and workers (Sippel and Jenssen, 2009) ‱ the presence of state and federal mandates or initiatives (Wallis, 2011;Tang et al, 2010).…”
Section: Overview Of Responses To Climate Change In Urban Areas Of Thmentioning
confidence: 99%